Inhibition of histone deacetylases attenuates tumor progression and improves immunotherapy in breast cancer - Lian, Bi; Chen, Xiaosong; Shen, Kunwei (Frontiers in Immunology, 2023)
Breast cancer is one of the common malignancies with poor prognosis worldwide. The treatment of breast cancer patients includes surgery, chemotherapy and immunotherapy. In recent years, immunotherapy has potentiated the survival of certain breast cancer patients; however, primary resistance or acquired resistance attenuate the therapeutic outcomes. Histone acetyltransferases induce histone acetylation on lysine residues, which can be reversed by histone deacetylases (HDACs). Dysregulation of HDACs via mutation and abnormal expression contributes to tumorigenesis and tumor progression. Numerous HDAC inhibitors have been developed and exhibited the potent anti-tumor activity in a variety of cancers, including breast cancer. HDAC inhibitors ameliorated immunotherapeutic efficacy in cancer patients. In this review, we discuss the anti-tumor activity of HDAC inhibitors in breast cancer, including dacinostat, belinostat, abexinostat, mocetinotat, panobinostat, romidepsin, entinostat, vorinostat, pracinostat, tubastatin A, trichostatin A, and tucidinostat. Moreover, we uncover the mechanisms of HDAC inhibitors in improving immunotherapy in breast cancer. Furthermore, we highlight that HDAC inhibitors might be potent agents to potentiate immunotherapy in breast cancer.